Enhancing Community Resilience in Padang’s Coastal Slums through the Disaster Imagination Game (DIG) (Jurnal Perencanaan Pembangunan: The Indonesian Journal of Development Planning, 2025)
Coastal slums in Padang, Indonesia, face severe exposure to earthquakes, tsunamis, and compounding hazards such as fires and tidal flooding. Despite the devastating experiences of past disasters, particularly the 2009 earthquake, these communities remain highly vulnerable due to limited infrastructure, dense housing, and restricted evacuation access. Addressing such conditions requires approaches that not only raise awareness but also actively involve residents in preparedness planning. This study explores the application of the Disaster Imagination Game (DIG) as a participatory method to strengthen community-based disaster risk reduction (CBDRR) in two subdistricts, Rimbo Kaluang and Flamboyan Baru. A community workshop was organized to engage residents in hazard mapping, evacuation route identification, and scenario-based disaster simulations. The DIG process revealed specific challenges, such as blocked alleyways and bottlenecks in Rimbo Kaluang, and recurrent tidal flooding that intersects evacuation paths in Flamboyan Baru. At the same time, it generated shared priorities across both communities, including the installation of evacuation signage, development of community-based early warning systems, regular drills, and reinforcement of non-engineered housing. Beyond enhancing disaster awareness, DIG fostered dialogue and trust between residents, community leaders, and government stakeholders, effectively bridging local knowledge with formal planning processes. The findings highlight DIG as a low-cost, adaptable, and scalable tool that can inform urban planning, slum upgrading programs, and local disaster preparedness policies. Integrating DIG into municipal planning frameworks offers a practical pathway to strengthen resilience in Indonesia’s high-risk urban settlements.